2012
DOI: 10.1063/1.4769214
|View full text |Cite
|
Sign up to set email alerts
|

The c-axis thermal conductivity of graphite film of nanometer thickness measured by time resolved X-ray diffraction

Abstract: We report on the use of time resolved X-ray diffraction to measure the dynamics of strain in laser-excited graphite film of nanometer thickness, obtained by chemical vapour deposition (CVD). Heat transport in the CVD film is simulated with a 1-dimensional heat diffusion model. We find the experimental data to be consistent with a c-axis thermal conductivity of ∼0.7 W m−1 K−1. This value is four orders of magnitude lower than the thermal conductivity in-plane, confirming recent theoretical calculations of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
42
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 23 publications
8
42
1
Order By: Relevance
“…This can be attributed to the three-dimensional graphene framework of high thermal conductivity in the composites prepared by latex mixing. However, the increase in thermal conductivity of the composites is far lower than is expected when considering the ultra-high inplane thermal conductivity of graphene [39]. Similar results have also been reported by some other groups.…”
Section: Resultssupporting
confidence: 89%
“…This can be attributed to the three-dimensional graphene framework of high thermal conductivity in the composites prepared by latex mixing. However, the increase in thermal conductivity of the composites is far lower than is expected when considering the ultra-high inplane thermal conductivity of graphene [39]. Similar results have also been reported by some other groups.…”
Section: Resultssupporting
confidence: 89%
“…27 This indicates that phonons with MFP beyond 15 nm still have significant contribution to k c . Furthermore, recent experimental work 29 showed that k c of a graphite thin film with thickness of $35 nm is only $0.7 W/m K, which is much lower than the well-accepted bulk value of $5.7 W/m K. 30 In fact, one recent publication 31 has shown that the c-axis phonon MFP could be as long as 20 nm. Moreover, to explain our experimental observation of the contact thermal conductance between multi-walled carbon nanotubes, Yang et al 32 estimate that the phonon MFP along the c-axis of graphite could be well above 100 nm at room temperature.…”
mentioning
confidence: 97%
“…Sadeghia et al evidence of boundary scattering of phonons with MFPs much longer than 35 nm [28]. Using molecular dynamics simulations, Wei et al [29].…”
mentioning
confidence: 99%